A COMPARISON OF 0.5% BUPIVACAINE ALONE VERSUS 0.5% BUPIVACAINE WITH VERAPAMIL AS AN ADJUNCT IN ULTRASOUND-GUIDED SUPRACLAVICULAR BRACHIAL PLEXUS BLOCK - ASHWIN KUMAR; SUNEETA DUTTA; SANGITA YADAV (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: Supraclavicular brachial plexus blocks are commonly performed for surgeries on the upper limb because they are highly effective for both anesthesia during the procedure and pain control afterward. This method targets the entire brachial plexus, making it a popular alternative to general anesthesia, as it minimizes associated risks while offering better pain relief after the surgery. Bupivacaine, a long-lasting local anesthetic, is often preferred for this block, though its pain-relieving effects eventually wear off. Owing to limitations regarding the duration of analgesia, many adjuncts have been tried since time immemorial to enhance the effectiveness of the blocking properties of these local anesthetics. Verapamil, a calcium channel blocker, has emerged as a promising adjunct that can potentially enhance and prolong the effects of Bupivacaine. This study aims to compare the efficacy of 0.5% Bupivacaine alone versus Bupivacaine combined with Verapamil in ultrasound-guided supraclavicular brachial plexus blocks. Methods: A randomized clinical trial was conducted on patients undergoing elective upper limb surgeries under ultrasound-guided supraclavicular brachial plexus block. Group A received 30 mL of 0.5% Bupivacaine, whereas Group B received 30 mL of 0.5% Bupivacaine with 5 mg of Verapamil. Primary outcomes included the time of onset of sensory and motor blockade and the duration of analgesia for the same, whereas secondary outcomes included post-operative pain scores and hemodynamic stability. Results: The addition of Verapamil to Bupivacaine significantly accelerated the onset of sensory and motor blockade in Group B compared to Group A. Group B also exhibited a significantly prolonged duration of both sensory and motor blockade and reduced post-operative analgesic requirements. Conclusion: Verapamil helps boost the effectiveness of Bupivacaine in supraclavicular brachial plexus blocks, speeding up the onset of its actions and extending its pain-relieving effects. This makes it a useful addition to local anesthetics, making it a valuable adjunct in regional anesthesia.